(3fKQ GdLeGf aj TYQ ef fXefj hEjGg GdReGfs - (3GHf GdGMeQ , ESeGYjd Hf jhSa Hf eMeO Hf fUQ GdNRQLj GdfUQj, CHh GdhdjO,J (B807 (3g` s
(3ChdgG (B:s
(3hHYO, aEfg deG cGf GdTYQGA hHhHJg CMO YTQ HGHkG GdHGH GdChd aj aVd GdTYQ s
(3BNQgG (B:s
(3eHJhQ, hBNQ GdehLhO efgG bhdg(B: (3hCfTOfj CjVkG hCfG EP PGc LGdS aj Pdc GdehVY GJfRg aj bJd GdCShO s
(3GfXQ aj GdLRA GdChd Qbe (B850 (3COHs
(3aj CMO YTQ HGHkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B130 s
Keywords: (3GdCOHs